Traditional medicinal plants used by indigenous people of Deder district, east Hararghe Zone of Oromia, Ethiopia - Egigu, Meseret C; Ketema, Mulatu; Sasikumar, Jagathala M. (Ethnobotany Research and Applications, 2026)
Background: In Ethiopia, mismanagement of natural ecosystems is jeopardizing traditional medicinal plants and the associated indigenous knowledge. This study reports local us practices of traditional medicinal plants by indigenous people of Deder district, Ethiopia for preservation. Methods: Data were collected using semi-structured interviews, focus group discussion and field visits. Ethnobotanical indices, t-test, Mann-Whitney U test and one-way ANOVA were data analysis methods used to reveal agreements between respondents and the impacts of socio-demographic factors on respondents’ ethnomedicinal knowledge. Results: Totally, 100 medicinal plant species belonging to 51 families were documented along with their medicinal use practices by the indigenous people. Asteraceae and Lamiaceae were species rich families. Herbs constituted the highest proportion followed by shrubs and trees. Leaves were frequently reported plant parts. Remedy preparation methods were mainly crushing, pounding, or powdering depending on the specific characteristics and conditions of the plant parts to concoct or decoct. The most reported route of remedy administration was oral followed by topical application. Febrile and fever disease category scored highest ICF value. Senecio hadiensis and Hagenia abyssinica scored 100% FL for treating rheumatism and colds, respectively. Croton macrostachyus was the most preferred plant to treat rabies. There was no statistically significant (p=0.196) difference between kebeles in terms of number of medicinal plants reported. Number of medicinal plants reported was significantly (p<0.01) affected by age and educational level. Conclusions: Alongside modern medication, local community of Deder district depend considerably on traditional medicine. Thus, these plants should be given conservation attention and be evaluated pharmacologically. Keywords: Ethnobotany; Ethnomedicine; Indigenous knowledge; Medicinal plants